Validity and Reliability of Sports Motor Competency Assessment for High School Students in an Educational Context - Pardilla, Herli; Nofrizal, Dedi; Isnandar, Muhammad; Duha, Netral; Firoza, Nayna; Syafna, Jihan; Gordichev, Velorine (Journal of SPORT (Sport, Physical Education, Organization, Recreation, and Training), 2025)
Motor competency is a foundational component of adolescent physical development, influencing both health outcomes and long-term activity participation. However, evidence on the reliability of comprehensive motor skill assessments in Indonesian high schools remains limited. This study aimed to evaluate the test–retest reliability of a six-item sports motor competency battery in Indonesian high school students. Sixty adolescents (aged 15–17) from Perbaungan, North Sumatra, completed standardized assessments including sprint, vertical jump, agility, push-up, sit-and-reach, and medicine ball throw tests. A one-week interval separated repeated trials, and Intraclass Correlation Coefficients (ICC), Standard Error of Measurement, and Bland–Altman analyses were employed. Results demonstrated excellent reliability across all measures (ICC = 0.89–0.97) with minimal measurement error and no gender differences. Small but non-significant learning effects were observed in vertical jump and push-up performance. These findings confirm that the battery provides consistent, dependable metrics suitable for physical education monitoring, talent identification, and longitudinal adolescent motor competency research.